Higher Education in India in the Time of Pandemic, Sans a Learning Management System - Sudipta Roy; Shannon Brown (SAGE Publishing, 2022)
Higher education in India was caught completely unawares by the COVID-19 pandemic and the necessitated closure of educational institutions. Despite almost a decade of experience with online and distance learning at some top-tier and private institutions, the vast majority were unprepared and looked for quick solutions for different components of teaching-learning depending on the need of the hour. The immediate tool sought was a videoconferencing platform to substitute in-class lectures. With no access to a learning management system, faculty chose one platform for videoconferencing, one for interaction with students, and another for uploading class notes. Disparity in students' access to devices and the internet presented challenges. Assessment of learning, which hitherto was largely pen and paper based, was delayed for lack of a viable solution. Experiences documented in this study demonstrate faculty resilience, but lack of institutional leadership and preparedness is starkly evident.